Safety of intranasal insulin administration in patients undergoing cardiovascular surgery: An open-label, nonrandomized, dose-escalation studyCentral MessagePerspective - Yosuke Nakadate, MD, PhD; Akiko Kawakami, MD, PhD; Takeshi Oguchi, MD, PhD; Keisuke Omiya, MD, PhD; Hiroyuki Nakajima, MD, PhD; Hiroshi Yokomichi, MD, PhD, DPH; Hiroaki Sato, MD, PhD; Thomas Schricker, MD, PhD; Takashi Matsukawa, MD, PhD (JTCVS Open, 2024)
Objective: This study aimed to determine the maximum safe dose of intranasal insulin administration during cardiac surgery. Methods: This open-label, Phase 1, single-center, dose-escalation clinical trial recruited patients scheduled to undergo elective cardiac surgery or major vascular surgery requiring cardiopulmonary bypass between February and September 2021. They were grouped into 5 dose-escalation cohorts and administered 0, 40, 80, 160, and 240 IU insulin (n = 6 in each group) via a metered nasal dispenser after the induction of general anesthesia. Blood samples were collected at 10-minute intervals for the first 60 minutes and at 30-minute intervals thereafter. Hypoglycemia was defined as a blood glucose level <70 mg/dL. Patient recruitment was terminated after hypoglycemia was observed in 2 patients in any of the groups. Results: In total, 27 of 29 enrolled patients were administered intranasal insulin or saline. Hypoglycemia was not observed after the administration of intranasal insulin in the 0, 40, 80, or 160 IU groups; however, it was observed in 2 of 3 patients in the 240 IU group. The serum insulin concentration was elevated in the 160-IU group, but the C-peptide concentration was not elevated in any of the groups. Conclusions: The administration of up to 160 IU intranasal insulin did not induce clinically significant hypoglycemia. However, 160 IU intranasal insulin should be administered cautiously because insulin can enter the systemic circulation in a dose-dependent manner.